1994
DOI: 10.1161/01.cir.90.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive thrombolytic therapy during angioplasty for ischemic rest angina. Results of the TAUSA Trial. TAUSA Investigators. Thrombolysis and Angioplasty in Unstable Angina trial.

Abstract: for the TAUSA Investigators Background Acute closure is increased after angioplasty in unstable angina, and adjunctive intracoronary thrombolytic therapy has been used successfully to increase angiographic success. The role of prophylactic thrombolytic therapy during angioplasty in unstable angina is unknown.Methods and Results Four hundred sixty-nine patients with ischemic rest pain with or without a recent (<1 month) infarction were randomized in double-blind fashion to intracoronary urokinase or placebo. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…Therefore, these patients might be exposed to the bleeding risks associated with thrombolytic therapy without its beneficial effect [9]. Moreover, it has been speculated that the procoagulant effects of thrombolytic therapy could convert a nonocclusive thrombus to an occlusive thrombus [9], as was observed in the TIMI-IIIB trial [10]and the TAUSA study [11]in patients with unstable angina treated with tPA and urokinase, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these patients might be exposed to the bleeding risks associated with thrombolytic therapy without its beneficial effect [9]. Moreover, it has been speculated that the procoagulant effects of thrombolytic therapy could convert a nonocclusive thrombus to an occlusive thrombus [9], as was observed in the TIMI-IIIB trial [10]and the TAUSA study [11]in patients with unstable angina treated with tPA and urokinase, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although thrombolytics have been shown to restore vessel patency when thrombus develops during angioplasty and progresses to complete vessel occlusion, this clinical scenario is still associated with a high incidence of complications [15][16][17][18][19][20]. Finally, recent data has suggested that the antecedent administration of thrombolytic agents may in fact be detrimental in the percutaneous treatment of patients with unstable angina [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, placement of a stent in the midst of the thrombus may further aggravate the thrombosis with subsequent vessel closure. Thrombolytic agents given before or during the angioplasty have been tried with very unsatisfactory results [3]. Glycoprotein IIbIIIa receptor antagonists have been shown to improve outcomes in high risk angioplasty, but in the setting of heavy thrombus, the results are equivocal [4].…”
Section: Introductionmentioning
confidence: 99%